Kesadaran Mahasiswa Terhadap Nilai Disiplin Dalam Menyelesaikan Tugas Perkuliahan - Antonius A. Saetban (Peneliti.net, 2022)
Discipline behavior for students is one of the keys to success to be able to achieve maximum achievement. The main function of discipline is a form of responsibility to control oneself by respecting and obeying the rules. The purpose of this study was to find out how students manage lecture time in completing lecture assignments. The benefit is to help students make maximum use of time as well as input for institutions in this case the UNTRIB Kalabahi campus to design programs related to disciplinary issues in providing assistance and guidance for students. The method used in this research is descriptive qualitative conducted to describe a phenomenon, event, and events that occur factually, systematically, and accurately. The location of this research took place on the Tribuana Kalabahi University Campus with 75 respondents being the fourth semester students of the Elementary School Teacher Education Study Program. The results of the study concluded that the fourth semester students of Tribuana Kalabahi University lacked discipline in completing lecture assignments. Research data shows that in terms of learning discipline, 57% of respondents answered that they were not disciplined in completing lecture assignments with internal reasons being lazy, not having awareness, wanting to relax, being indifferent, sleeping more